1983
DOI: 10.1002/ajmg.1320140307
|View full text |Cite
|
Sign up to set email alerts
|

Short rib‐polydactyly syndrome, Majewski type

Abstract: We describe a baby with external and internal anomalies of the Majewski form of the short rib-polydactyly (SRP) syndromes. Previously unreported abnormal vertebral bodies, delayed ossification of the sternum and fibulae, and a diencephalic hamartoma are noted. These abnormalities and minimal histologic abnormality at the chondro-osseous junction suggest that this syndrome may be heterogeneous or more variable than previously known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The SRP syndromes are a minefield for splitters and lumpers because the clinical and radiological overlap of the different types often leads to difficulties in classification. Many have argued that the different types of SRP syndromes are due to genetic heterogeneity [Walley et al, 1983], or different allelic mutations and secondary intrauterine modification of the condition [Bernstein et al, 1985]. The lumpers have presented a case for a single genetic disorder with a widely variable clinical expression [Sillence et al, 1987; Tsai et al, 1992; Elcioglu and Hall, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…The SRP syndromes are a minefield for splitters and lumpers because the clinical and radiological overlap of the different types often leads to difficulties in classification. Many have argued that the different types of SRP syndromes are due to genetic heterogeneity [Walley et al, 1983], or different allelic mutations and secondary intrauterine modification of the condition [Bernstein et al, 1985]. The lumpers have presented a case for a single genetic disorder with a widely variable clinical expression [Sillence et al, 1987; Tsai et al, 1992; Elcioglu and Hall, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…They recommended the eponym "Beemer-Langer" and used the abbreviation SR(P)S to indicate variable polydactyly. Though different subtypes of SRPS was proposed to clarify this confusing syndrome [Spranger and Maroteaux, 19901, some authors have suggested that the SRPS are a single entity with varying expressivity [Bidot-Lopez et al, 1978;Silence, 1980;Walley et al, 1983;Bernstein et al, 19851. We report on a case that cannot be definitely categorized into the above mentioned forms, yet possesses some of the manifestations of al1 forms. These observations seem to support the contention of a single entity with varying expressivity.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients formerly presented as MS [Le Marec et al, 1982;Black et al, 1982;Walley et al, 1983;Garcia et al, 19881 or as unverified forms of the short rib-polydactyly syndromes [Afzal et al, 1979;Shih et al, 19831 may indeed have BLS.…”
Section: Resultsmentioning
confidence: 99%
“…At least 13 patients with the BLS had cleft tongue, oral frenula, and/or natal teeth [Afzal et al, 1979;Black et al, 1982;Le Marec et al, 1982;Walley et al, 1983;Yang et al, 1987 (patient 4); Garcia et al, 1988;Hingorani et al, 1991;Lin et al, 1991;Yang et al, 1991;Encha-Razavi et al, 1992;Brenner et al, 19931. These defects (as well as cleft lip and preaxial polydactyly of the feet) are also common in the autosomal recessive inherited oro-facio-digital syndromes types IV (associated with short limbs with predominant shortness of the tibia) or VI (associated with agenesis or hypoplasia of the cerebellar vermis) [Munke et al, 1990;Nevin et al, 19921.…”
Section: Resultsmentioning
confidence: 99%